2020
DOI: 10.1038/s41598-020-62062-3
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Cellular Toxicity of Pathogenic or Non-pathogenic Proteins

Abstract: More than 20 unique diseases such as diabetes, Alzheimer’s disease, Parkinson’s disease are caused by the abnormal aggregations of pathogenic proteins such as amylin, β-amyloid (Aβ), and α-synuclein. All pathogenic proteins differ from each other in biological function, primary sequences, and morphologies; however, the proteins are toxic when aggregated. Here, we investigated the cellular toxicity of pathogenic or non-pathogenic protein aggregates. In this study, six proteins were selected and they were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…In contrast, the overexpression of PD-L1 in PCI 52 with an abundant intrinsic PD-L1 expression led to a decrease in cell spreading on collagen type I and Matrigel ® . This might be due to the overload of PD-L1 expression (intrinsic plus overexpression), where cells have to prevent the aggregation of excessive proteins, which is toxic for cells at a certain concentration [44]. On the other hand, the siRNA knockdown of PD-L1 led to the decreased spreading of all HNSCC spheroids independent of surface coatings.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the overexpression of PD-L1 in PCI 52 with an abundant intrinsic PD-L1 expression led to a decrease in cell spreading on collagen type I and Matrigel ® . This might be due to the overload of PD-L1 expression (intrinsic plus overexpression), where cells have to prevent the aggregation of excessive proteins, which is toxic for cells at a certain concentration [44]. On the other hand, the siRNA knockdown of PD-L1 led to the decreased spreading of all HNSCC spheroids independent of surface coatings.…”
Section: Discussionmentioning
confidence: 99%
“…28,57 In contrast, misfolded, oligomeric pathogenic and nonpathogenic proteins or even small organic molecules forming colloidal aggregates can provoke interactions that often prove cytotoxic. [58][59][60][61] Promiscuous interactions in the extracellular spaces could potentially disrupt synaptic signaling and channel proteins. The most likely prodomain interaction in this context is SorCS2, that exists as a dimer, as assessed by X-ray crystallography and negatively stained electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…8,15 Bovine serum albumin (BSA) is considered as one of the model amyloidogenic proteins for studying amyloid aggregation under in vitro conditions, 16,17 which has provided important information on the structural, biophysical, and cytotoxic properties of amyloid formation in non-pathogenic proteins. [7][8][9]18 Studies have revealed that the level of serum albumin is inversely linked with Aβ deposition and Aβ positivity. 19 Research reports have also shown that Aβ [25][26][27][28][29][30][31][32][33][34][35] can induce in vitro cross-seeding of BSA, resulting in aggregates that were toxic to microglial cells.…”
Section: ■ Introductionmentioning
confidence: 99%